Carbon dots labeled Lactiplantibacillus plantarum: a fluorescent multifunctional biocarrier for anticancer drug delivery - Abdullah, Noor A.; Mahmoud, Hoda E.; El-Nikhely, Nefertiti A.; Hussein, Ahmed A.; El-Khordagui, Labiba K. (Frontiers in Bioengineering and Biotechnology, 2023)
A carbon dots (CDs)-biolabeled heat-inactivated Lactiplantibacillus plantarum (HILP) hybrid was investigated as a multifunctional probiotic drug carrier with bioimaging properties using prodigiosin (PG) as anticancer agent. HILP, CDs and PG were prepared and characterized using standard methods. CDs-labeled HILP (CDs/HILP) and PG loaded CDs/HILP were characterized by transmission electron microscopy (TEM), laser scanning confocal microscopy (LSCM) and for entrapment efficiency (EE%) of CDs and PG, respectively. PG-CDs/HILP was examined for stability and PG release. the anticancer activity of PG-CDs/HILP was assessed using different methods. CDs imparted green fluorescence to HILP cells and induced their aggregation. HILP internalized CDs via membrane proteins, forming a biostructure with retained fluorescence in PBS for 3 months at 4°C. Loading PG into CDs/HILP generated a stable green/red bicolor fluorescent combination permitting tracking of both drug carrier and cargo. Cytotoxicity assay using Caco-2 and A549 cells revealed enhanced PG activity by CDs/HILP. LCSM imaging of PG-CDs/HILP-treated Caco-2 cells demonstrated improved cytoplasmic and nuclear distribution of PG and nuclear delivery of CDs. CDs/HILP promoted PG-induced late apoptosis of Caco-2 cells and reduced their migratory ability as affirmed by flow cytometry and scratch assay, respectively. Molecular docking indicated PG interaction with mitogenic molecules involved in cell proliferation and growth regulation. Thus, CDs/HILP offers great promise as an innovative multifunctional nanobiotechnological biocarrier for anticancer drug delivery. This hybrid delivery vehicle merges the physiological activity, cytocompatibility, biotargetability and sustainability of probiotics and the bioimaging and therapeutic potential of CDs.